Challenges and possibilities when doing research on active school travel interventions in a school setting - a non-randomized pilot study assessing feasibility of an evaluation design - Mathias Andersson; Elena Tseli; Anna-Karin Lindqvist; Stina Rutberg; Annie Palstam (BMC Public Health, 2025)
Abstract Background A wide range of school interventions have been launched to increase childrens’ physical activity. Evaluation of the effectiveness of interventions requires suitable study designs and feasible quantitative evaluations relating to the school setting. The purpose of this study was to assess the evaluation design and methods for data collection, in order to make decisions about approaching forthcoming studies of the effectiveness of active school travel (AST) interventions. Methods Children from four Swedish schools in fifth grade (11–12 years old) participated in this non-randomized pilot study, two schools received an AST intervention and two schools were controls. The school-based AST intervention Sustainable Innovation for Children Transporting Actively (SICTA) was conducted by teachers in the classroom setting during four weeks. To assess feasibility of the evaluation design and methods for data collection a combination of quantitative and qualitative methods were applied, using participation- and response rates, a feasibility questionnaire and focus group interviews. Results Out of 25 potential schools, four schools accepted participation with explicit allocation requests preventing randomization. Out of 181 children, 107 children (59%) accepted participation. A total of 82% of the participating children reported active travel before the AST intervention, and 80% found reporting of daily school travels in the web-based survey to be easy. The children were in general positive about participating in the study and the methods for data collection were considered easy for the participating children to conduct and to blend well with usual school activities. There was an imbalance in reporting rates between intervention and control schools as well as a decrease in reporting rates during the study period. Conclusions Our results highlight the complexity and challenges in conducting controlled research among school children. Although children were positive about participation and found reporting to be easy, our results invoke the need to use alternative research designs and recruitment strategies that also attract children using non-active modes of travel when evaluating AST interventions in school contexts. Trial registration The study is registered 2023/11/02 with Researchweb, the Swedish Register for Research with registration number 281,543. The registration can be reached via this link: https://www.researchweb.org/is/sverige/project/281543 .